PEMBUATAN NATA DE PINA DARI SUBSTRAT LIMBAH BUAH NENAS BERDASARKAN LAMA FERMENTASI SEBAGAI RANCANGAN MODUL PEMBELAJARAN BIOLOGI DI SMA - Guntur, Geby Zaryani; ', Darmawati; Mahadi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aimed to know making Nata de pina from waste of pineapple substrates on April until June 2016. Result of research was used as a learning module design in Biology of Senior High School. This research was conducted on two stage, were experiment stages and learning module design stage. Research of experiment was conducted with non factorial completely randomized design that consist 4 treatments and 3 replicates and totally obtain 12 experimental design. If there is a real difference, it will proceed further Duncan Multiple Range Test. The parameters was observed include the crude fiber content, the thickness and the organoleptic that include texture, smell, color and flavor. Result of research showed that long fermentation influence significantly to the crude fiber content and the thickness of Nata de pina from waste of pineapple. The 16th day of long fermentation were produced crude fiber content, the thickness, texture and the highest level of satisfaction. The result of crude fiber content is 2,63% and the result of thickness is 1,52 cm. This result of research as a learning module design in Biology of Senior High School as well as a source of learning for students in Senior High School especially in the matter of Conventional Biotechnology.Keywords: Nata de pina, Waste of Pineapple Substrates, Long Fermentation, Learning Module